Memelihara Kepercayaan Dan Reputasi Medical Tourism Indonesia: Regulasi Etika Medis, Perijinan, Dan Perlindungan Konsumen - Maryono (Perspektif Administrasi Publik dan hukum, 2024)
This paper discusses efforts to maintain the trust and reputation of the Medical Tourism industry in Indonesia. The industry has grown rapidly in recent years, with many international patients coming to Indonesia for medical treatment. The success of this industry relies heavily on consumers' trust in the quality of medical services and the protection they receive throughout the treatment process. Medical ethics, licensing and consumer protection regulations play a key role in ensuring that international patients receive safe, quality and ethical care in Indonesia. Medical ethics regulations will regulate the behavior of medical professionals and direct the standards of care that must be adhered to. Licensing functions as a mechanism for monitoring and controlling the quality of medical facilities and existing medical practices. Meanwhile, consumer protection is important to ensure that patients' rights are maintained during the treatment process, including the right to accurate information, transparent procedures and fair dispute resolution. In the context of Medical Tourism, reputation plays a central role. A good reputation will attract more international patients and help build long-term relationships with satisfied patients. However, reputation is also susceptible to negative changes due to bad patient experiences or violations of medical ethics. Therefore, efforts to prevent, manage and recover from adverse situations are very important in maintaining the industry's reputation.In the Indonesian context, harmonization between medical ethics regulations, licensing and consumer protection needs to be improved to create an environment that supports the sustainable growth of the Medical Tourism industry. The involvement of all stakeholders, including governments, medical institutions and medical professional associations, is key to achieving this goal. By maintaining service quality, high medical ethics, and effective consumer protection, Medical Tourism Indonesia can continue to develop and maintain a good reputation in the eyes of the international community.